Design and implementation of tri-band microstrip antenna - Chebil, Jalel; Habaebi, Mohamed Hadi; Noori, Omar; Khan, Sheroz; Islam, Md Rafiqul (Electrical Engineering Department, University of Nevada, 2019)
Multi-band antennas are becoming vital for wireless systems. This paper proposes a tri-band microstrip patch antenna using slots with h-shaped. The operating frequencies cover the GSM900, DCS1800 and the 2.4 GHz bands. The optimization of the antenna dimensions was obtained by using available tools in the CST microwave studio software. A prototype antenna was fabricated and tested. From the simulated and measured results, the antenna operational frequencies were achieved. It is also found that the gain and the return losses of the antenna were better than other letter-shaped antennas reported in the literature.